Structural characterizarion of extensive farms in Andalusian dehesas - García, A.; Perea, J.; Acero, R.; Angón, E. (Arch. Zoot, 2010)
Three types of livestock farming systems are identified in Andalusian dehesas using multivariate analysis. One of two conservationist systems, both applying sustainable management criteria, was detected in most of farms: dehesa farming system (49% of farms): small extensive cattle and sheep farms, which adapt stocking rates to the availability of the land's natural resources, and occasional use of strategic food supplementation; mountain farming system (21%) also relative to small farms, with mainly small ruminants and limited use of technology. The third system was a yield targeted system (30%), corresponding mainly to large cattle farms, with greater use of technology and high levels of food supplementation caused by stocking rates that exceed the land's carrying capacity. Typology defined can be used as starting point to base technical and economic characterization of farming systems taking into consideration their current and future viability
Keywords: Factorial analysis; Farm typology; Livestock farming systems

Caracterización productiva del vacuno ecológico en Andalucía - Perea Falcón, J.; García, Ana; Acero, R.; Valerio, Daniel; Rodríguez, V. (Arch. Zootec, 2007)
The structure of organic beef cattle farms located in Andalusia have been characterised from a stratified survey including 10% of official census. Farms are specialized in raising steers and use native breeds. The mean surface of farms is 524 ha and they have 99 cows. They are multifunctional systems located in the dehesa, where cattle commonly graze alongside other species like Iberian pigs. These farms correspond to a production model in which the land is extremely important in the production of food for the cattle, using strategic or seasonal food supplementation in periods of shortage. Average stocking is 0.43 animals/ha, lower than those proposed by Orden de 4 de febrero del 2004 (Consejería de Agricultura y Pesca), corresponding to a farming activity adapted to the environment. Likewise, the mean productivity of these farms is scarce (with an index of commercial calves of 80% and a mortality rate of 5.26%). These farms have a commercial target where the non-familiar workforce predominates, and the workforce amounts to 1.56 AWU per farm. These farms sell all calves after weaning to livestock traders, who take them to other regions for conventional fattening until slaughter. It is necessary to develop organic commercial trails to guarantee the future of the sector.
Keywords: Beef aptitude; Extensive systems; Organic farming